Pemanfaatan Program Microsoft Mathematic Dan Geogebra Untuk Peningkatan Mutu Guru Matematika Tingkat SMP Di Kabupaten Bantaeng Sulawesi Selatan - Mahie, Andi Galsan; Haryanto, Loeky; Azis, Moh Ivan; Massalesse, Jusmawati; Jaya, Andi Kresna (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2019)
outcomes generated from this activity are as follows: 1) Enhance the ability of Partners in developing existing technology, especially computers in optimizing learning in the classroom through the Geogebra and Microsoft Mathematic programs. Middle School Mathematics Teachers in Bantaeng District are trained in making teaching materials, especially computer-based self-learning modules that are not only material and questions but must be able to develop children's abilities in constructing the concept of the material being taught. The Geogebra and Microsoft Mathematic programs are application programs that can be utilized in dealing with these problems; 2) Training for teachers who are members of the Bantaeng District Junior High School Mathematics Teacher (MGMP). The training material was in the form of a guidebook for the use of the Geogebra program and the Microsoft Mathematics and its use in mathematics learning developed by the Mathematics Department FMIPA UNHAS dedication team. The teaching materials will be used in the training as an initial stage for the teachers to recognize and master the Geogebra and Microsoft Mathematics programs.